New Exact Soliton Solutions of the (3+1)-Dimensional Conformable Wazwaz–Benjamin–Bona–Mahony Equation via Two Novel Techniques - Mohammed K. A. Kaabar; Melike Kaplan; Zailan Siri (Journal of Function Spaces)
In this work, the (3+1)-dimensional Wazwaz–Benjamin–Bona–Mahony equation is formulated in the sense of conformable derivative. Two novel methods of generalized Kudryashov and exp−φℵ are investigated to obtain various exact soliton solutions. All algebraic computations are done with the help of the Maple software. Graphical representations are provided in 3D and 2D profiles to show the behavior and dynamics of all obtained solutions at various parameters’ values and conformable orders using Wolfram Mathematica.